Hemochromatosis gene mutations and iron metabolism in celiac disease - D Barisani; S Ceroni; S Del Bianco; R Meneveri; MT Bardella (Haematologica, 2004)
BACKGROUND AND OBJECTIVES: Iron deficiency anemia is a common manifestation of celiac disease, which may be due to genetic and environmental factors. HFE mutations, frequent in Caucasian populations, can cause increased intestinal iron absorption and thus could protect against the development of iron deficiency. The aim of this study was to evaluate the prevalence of HFE mutations and their effect on iron metabolism in Italian celiac patients at diagnosis and after a gluten-free diet. DESIGN AND METHODS: C282Y and H63D mutations were assessed by polymerase chain reaction (PCR) and restriction enzyme digestion in 203 patients with celiac disease and in 206 controls. HLA alleles were determined by sequence-specific primers and PCR. Duodenal histology was graded using Marsh's classification, and iron parameters measured by standard techniques. RESULTS: The frequency of the C282Y mutation was similar in celiac patients and controls (0.034 vs. 0.031); comparable frequencies were detected also for the H63D allele (0.170 vs. 0.136 in celiac patients and controls, respectively). Neither of the two HFE mutations affected iron indices in celiac patients at diagnosis, whereas a significant inverse correlation was detected between hemoglobin or ferritin and severity of histological damage (Marsh 3C or 3B vs. 3A, p